Comparison study between multimedia and simulation courseware toward students’ achievement based on different levels of motivation - Zol Bahri, Razali, Dr.; Shazmin Aniza, Abdul Shukor (Universiti Teknologi Malaysia (UTM), 2013)
Link to publisher's homepage at http://www.utm.my/